1972
DOI: 10.1136/oem.29.3.280
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of effects on macrophage cultures of glass fibre, glass powder, and chrysotile asbestos

Abstract: . (1972). Brit. J. industr. Med., 29,[280][281][282][283][284][285][286] Comparison of effects on macrophage cultures of glass fibre, glass powder, and chrysotile asbestos. The effects on macrophage cultures of glass fibre, glass powder, and chrysotile asbestos are compared. Glass fibre behaves like chrysotile in producing an increase in cell membrane permeability in cultured macrophages. This is demonstrable by the increase in lactic dehydrogenase activity in the supernatant fluid. The metabolism, measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1973
1973
2005
2005

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Koshi, Hayashi, and Sakabe (1968), by measuring acid phosphatase and production of lactic acid in macrophages, showed the different toxic effects of asbestos samples of different origin. Beck, Holt, and Manojlovic (1972) did not observe a depression of the lactic acid in chrysotiletreated macrophages but there was an increased number of cells with erythrosin and higher activity of the cytoplasmic enzyme lactate dehydrogenase. However, Parazzi, Pernis, Secchi, and Vigliani (1968) found a depression in the production of enzymes in crocidolite and chrysotile incubated macrophage cultures.…”
mentioning
confidence: 57%
“…Koshi, Hayashi, and Sakabe (1968), by measuring acid phosphatase and production of lactic acid in macrophages, showed the different toxic effects of asbestos samples of different origin. Beck, Holt, and Manojlovic (1972) did not observe a depression of the lactic acid in chrysotiletreated macrophages but there was an increased number of cells with erythrosin and higher activity of the cytoplasmic enzyme lactate dehydrogenase. However, Parazzi, Pernis, Secchi, and Vigliani (1968) found a depression in the production of enzymes in crocidolite and chrysotile incubated macrophage cultures.…”
mentioning
confidence: 57%
“…Unlike quartz powder it does not have a any guinea-pig treated with powdered glass. toxic effect and it does not cause the leakage of large quantities of lactic dehydrogenase from the Comment cell (Beck et al, 1972). The toxicity of quartz appears to be due to the chemical composition or nature of Glass powder affects macrophage cultures in a the surface of the dust.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro, crystalline particles can be modified in the lysosomes of cultured macrophages, e.g., for certain silicates, (talc; Handerson, 1975), (chrysotile and glass fibre; Beck, 1972), or for certain oxides (cobaltic oxide; André and Métevier, 1987), (uranium oxides;Poncy, 1992). Some authors have demonstrated that chrysolite fibres (Jaurand, 1977) as well as some industrial uranium oxides (Hengé-Napoli, 1994) can be dissolved in vivo.…”
Section: Data Concerning Insoluble Particlesmentioning
confidence: 99%